Strategy for reliable growth of thin GaN Caps on AlGaN HEMT structures - Saptarsi Ghosh (Journal of Crystal Growth, 2023)
This paper presents the growth of thin GaN capping layers on standard AlGaN HEMT structures. It has been found that the reliable growth of thin () GaN capping layers by organometallic vapour phase epitaxy is challenging as GaN is unstable at high growth temperatures even in atmospheres with high ammonia partial pressure. To overcome this challenge a growth strategy based on the controlled desorption of GaN has been adopted. By intentionally growing thicker than desired capping layers and controlling the desorption during the cool down after growth it is feasible to reliably grow high quality GaN capping layers with a specific target thickness. The development of the controlled desorption process has been simplified by predicting the desorption based on the computer controlled cooling ramp and the temperature dependent GaN desorption rate. The latter was obtained by analysing in-situ reflectance traces for relevant growth conditions. Moreover, examples on how to identify exposed AlGaN barriers, i.e. without intact GaN caps, by TEM and AFM are presented.